Characterization of aluminum gallium oxide films grown by pulsed laser deposition. Issue 1 (January 2019) - Yuan, Shuo-Huang; Ou, Sin-Liang; Chen, Chien-Ming; Huang, Shiau-Yuan; Hsiao, Bo-Wen; Wuu, Dong-Sing
Abstract: Aluminum gallium oxide (AGO) films were prepared on conventional c -plane sapphire by pulsed laser deposition (PLD). In the current PLD-AGO studies, target composition or growth temperature is usually the main deposition variable, and the other growth conditions are fixed. This would make it difficult to fully understand the theory and characterization of AGO films. In this study, several growth parameters such as target composition, gas atmosphere, laser repetition frequency, growth pressure, and substrate temperature (Ts ) were all modulated to realize and optimize the AGO growth. When the (Alx Ga1-x )2 O3 target with the Al content larger than 20 at% was used, a serious target poisoning phenomenon occurred, leading to the extremely unstable growth rate. In comparison to the AGO film grown with argon atmosphere, the higher transparency was reached in the film prepared with oxygen atmosphere due to the relative abundance of oxygen. Because of the homogeneous oxygen reduction, the AGO film with the higher crystal quality was obtained at a higher laser repetition frequency. With an increment of growth pressure, the Al content of AGO film was increased. The growth of AGO film at the higher Ts would cause the higher bandgap value, smoother surface, and growth rate degradation. Additionally, the crystal quality of AGO film can be also improved both by increasing the growth pressure and Ts . The better characterization can be reached in the AGO film grown using the (Al0.05 Ga0.95 )2 O3 target with oxygen atmosphere at the working pressure of 2 × 10 −1 Torr, the laser repetition frequency of 10 Hz, and the Ts of 800 °C. When the metal-semiconductor-metal photodetector fabricated with this AGO active layer, the best performance including the photocurrent of 7.56 × 10 −8 A, dark current of 1.59 × 10 –12 A, and photo/dark current ratio of 4.76 × 10 4 (@5 V and 240 nm) were achieved. Graphical abstract: Highlights: Aluminum gallium oxide (AGO) films were prepared by pulsed laser deposition. Several growth parameters were modulated to realize and optimize the AGO growth. Better properties are reached in the film grown using a (Al0.05 Ga0.95 )2 O3 target. Optimum working pressure and Ts are 2 × 10 −1 Torr and 800 °C, respectively. Photodetector with this AGO film has the highest photo/dark current ratio.